ISO 9001 and Business Performance: A Quantitative Study in Portuguese Organizations - Alcina Augusta de SENA PORTUGAL DÍAS; Iñaki HERAS-SAIZARBITORIA (Revista de Management Comparat International)
The effects of ISO 9001 quality certification process inside an organization may be considered on a wide range. This article places this phenomenon under a theoretical perspective and aims to analyze the impact of ISO 9001 quality standard on business performance according to the financial information data. More specifically, the impact of ISO 9001on productivity, business value and increase on sales is viewed through an econometric model of analysis concerning a panel data of Portuguese companies from the agro-food and to the construction sector. This analysis has presented interesting different results and in brief revealed that it may not be deterministically ascertained a direct connection between ISO 9001 certification and the improvement on business performance. Many other variables are committed to its success.